Allele specific DNAzyme assembly for fast and convenient SNP colorimetric genotyping directly from noninvasive crude samples. Issue 5 (18th January 2019) - Huang, Lizhen; Xia, Qianfeng; Zhang, Yuhong; Bai, Huili; Luo, Nini; Xiang, Linguo; Ding, Shijia; Cheng, Wei
Abstract : An allele specific DNAzyme assembly strategy was developed for fast and simple SNP genotyping directly from crude buccal swab samples without DNA extraction and purification. Abstract : Fast and convenient genotyping of single nucleotide polymorphisms (SNPs) is highly desirable for pharmacogenomics-based personalized medicine in settings where a centralized laboratory is not available. Herein, we developed an allele specific DNAzyme assembly (ASDA) strategy for fast and simple SNP colorimetric genotyping directly from crude buccal swab samples without DNA extraction and purification. Using the methylenetetrahydrofolate reductase (MTHFR) C677T allele as a model, novel allele specific primers were designed by introducing an optimized additional mismatch to eliminate cross amplification and tagging a G-quadruplex (G4)-containing hairpin tether to transform specific PCR amplification to numerous G4 DNAzyme assemblies. Based on this ASDA strategy, the proposed method can discriminate SNP alleles from as low as 200 cells, showing high sensitivity and excellent selectivity with a simple colorimetric assay, and showed remarkable accuracy, robustness and practicability for SNP genotyping directly from crude real samples with a total turnaround time of 90 min. The ASDA-based colorimetric assay presented a pragmatic platform toward simple and fast SNP genotyping in clinical laboratories, and a potential tool to improve the widespread application of personalized medicine, especially in developing areas.